2016
DOI: 10.1111/acps.12660
|View full text |Cite
|
Sign up to set email alerts
|

Can subsyndromal manifestations of major depression be identified in children at risk?

Abstract: These results suggest that the CBCL Anxiety/Depression scale can help identify children at highest risk for pediatric MDD. If implemented clinically, this scale would cost-effectively screen children and identify those most in need of early intervention resources to impede the progression of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Although children with parents who have had depression are at an elevated risk for developing depression, most children who develop depression do not come from families with an identified history of depression. 63 Further, the longitudinal nature of this study supports the validity of using RSNs to predict the worsening of psychiatric symptoms in childhood.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although children with parents who have had depression are at an elevated risk for developing depression, most children who develop depression do not come from families with an identified history of depression. 63 Further, the longitudinal nature of this study supports the validity of using RSNs to predict the worsening of psychiatric symptoms in childhood.…”
Section: Discussionsupporting
confidence: 62%
“…61,62 A subthreshold elevation on the anxiety/depression subscale of the CBCL in preadolescence predicts future development of MDD. 63 However, in conjunction with behavioral measures, neuroimaging measures may identify children at the greatest risk for developing psychiatric disorders with greater confidence and at an earlier age. Therefore, in this study, we investigated whether rs-fMRI data could predict future CBCL scores in a community sample of 54 children.…”
Section: Key Pointsmentioning
confidence: 99%
“…We recently showed that subsyndromal symptoms of MDD, as expressed in subsyndromal elevations of the Child Behavior Checklist (CBCL) Anxiety/Depression subscale, helped identify children at elevated risk for MDD within the pool of children at genetic risk by virtue of having a parent with MDD. 24 In that study, the 20% of children with subsyndromal scores on the CBCL Anxiety/Depression scale differed significantly from the other 80% of children at genetic risk for MDD in multiple non-overlapping correlates, including the development of MDD and other psychopathological conditions, as well as social and academic deficits. In contrast, children without this profile were indistinguishable from healthy controls on all measures assessed.…”
Section: Discussionmentioning
confidence: 83%
“…However, as this was a cross-sectional investigation, uncertainties remained as to whether this profile has predictive utility in helping forecast the clinical course for children at risk for MDD into adolescent and young adult years, a peak developmental period for the manifestation of MDD in youth. 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation